2022
DOI: 10.1021/acsomega.2c03511
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Controllable Synthesis of CuS@Ni-Co Layered Double Hydroxide Nanocages for Hybrid Supercapacitors

Abstract: The synthesis of battery-type electrode materials with hollow nanostructures for high-performance hybrid supercapacitors (HSCs) remains challenging. In this study, hollow CuS@Ni-Co layered double hydroxide (CuS-LDH) composites with distinguished compositions and structures are successfully synthesized by co-precipitation and the subsequent etching/ion-exchange reaction. CuS-LDH-10 with uniformly dispersed CuS prepared with the addition of 10 mg of CuS shows a unique hollow polyhedral structure constituted by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Their quantum confinement effects result in tunable bandgap energies, which enable them to absorb and emit light at specific wavelengths, making them suitable for use in different applications. [47,48] SQD-modified LDHs represent a novel hybrid material. When these LDHs are modified with SQDs, they offer unique synergistic properties.…”
Section: Synthesis Designing and Morphological Characterization Of La...mentioning
confidence: 99%
See 2 more Smart Citations
“…Their quantum confinement effects result in tunable bandgap energies, which enable them to absorb and emit light at specific wavelengths, making them suitable for use in different applications. [47,48] SQD-modified LDHs represent a novel hybrid material. When these LDHs are modified with SQDs, they offer unique synergistic properties.…”
Section: Synthesis Designing and Morphological Characterization Of La...mentioning
confidence: 99%
“…The research society has shown immense interest in utilizing the fullerenes dots for the fabrication of heterostructure material because of its unresolved physicochemical characteristics and stability. The incorporation of Fullerene QD into the LDH network could produce new attuned interfacial active sites consequently accelerating the electronic transfer between both LDH and Fullerene QD materials, thus improving the electrocatalytic properties of the nanohybrid material [47][48][49] By taking this fact, Wang et al designed a novel nano heterostructure composed of fullerene quantum dot anchored on a CoNi LDH nanosheet array self-supported on porous Ni foam (FQD/CoNiÀ LDH/NF) through a self-assembly hydrothermal method. By the advantages of a crumpled NF network, the CoNi LDH were split into small pieces supported by SEM Figure 11a and TEM image of the FQD/CoNiÀ LDH/NF nanohybrid.…”
Section: Carboneous Quantum Dots@ldhmentioning
confidence: 99%
See 1 more Smart Citation
“…After research, it is a solution to construct hollow nanostructures with internal voids, because they have the structural advantages of shortening the diffusion path of charge transmission and large surface permeability. Zhe Sheng et al [7] prepared CuS-LDH composites by coprecipitation method and etching/ion exchange method (Fig. 2), and successfully prepared various morphologies and structures on the basis of the additional quantity of CuS.…”
Section: Research and Application Of Transition Metal Compound Electr...mentioning
confidence: 99%
“…After research, it is a solution to construct hollow nanostructures with internal voids, because they have the structural advantages of shortening the diffusion path of charge transmission and large surface permeability. Zhe Sheng et al[7] prepared CuS-LDH composites by coprecipitation method and etching/ion exchange method (Fig.2), and successfully prepared various morphologies and structures on the basis of the additional quantity of CuS. They used CuS@ZIF-67-10 as precursor and sacrificial template to prepare CuS-LDH-10 with uniformly dispersed CuS which shows a unique hollow polyhedral structure composed of loose nanosphere units and these nanosphere units consist of staggered fine nanosheets, while vertically aligned NiCo-LDH nanosheets in CuS-LDH-30 grow on the surface of CUS shell to produce a hollow cubic structure.…”
mentioning
confidence: 99%